Pengaruh insentif terhadap peningkatan kinerja pustakawan di perpustakaan UNIMED - Tessa simahite (UIN Sumatera Utara, 2018)
This article discusses the effect of incentives on improving librarian performance in the UNIMED library. Based on the results of research on the effect of giving incentives to improve the performance of library librarians in Medan State University as follows: 1). There is a significant influence between giving incentives to improving the performance of the Library of Medan State Library with a calculated value of 0.679 and rtable of 0.334, meaning that r count> r table is 0.679> 0.33. And the discrimination coefficient (D) is 49.10%. 2). The results of the hypothesis obtained by tcount of 5.312 and t table of 1.70. From these results, the tcount> t table is 5.312> 1.70, so that the conclusions obtained in this study are that there is a significant influence between giving incentives to improving the performance of the Library of Medan State Library (Ha accepted and Ho rejected). Keywords: Performance, Librarians, Incentives, UNIMED